Failure mode and effects analysis: a comparison of two common risk prioritisation methods. Issue 5 (13th July 2015) - McElroy, Lisa M; Khorzad, Rebeca; Nannicelli, Anna P; Brown, Alexandra R; Ladner, Daniela P; Holl, Jane L
Abstract : Background: Failure mode and effects analysis (FMEA) is a method of risk assessment increasingly used in healthcare over the past decade. The traditional method, however, can require substantial time and training resources. The goal of this study is to compare a simplified scoring method with the traditional scoring method to determine the degree of congruence in identifying high-risk failures. Methods: An FMEA of the operating room (OR) to intensive care unit (ICU) handoff was conducted. Failures were scored and ranked using both the traditional risk priority number (RPN) and criticality-based method, and a simplified method, which designates failures as 'high', 'medium' or 'low' risk. The degree of congruence was determined by first identifying those failures determined to be critical by the traditional method (RPN≥300), and then calculating the per cent congruence with those failures designated critical by the simplified methods (high risk). Results: In total, 79 process failures among 37 individual steps in the OR to ICU handoff process were identified. The traditional method yielded Criticality Indices (CIs) ranging from 18 to 72 and RPNs ranging from 80 to 504. The simplified method ranked 11 failures as 'low risk', 30 as medium risk and 22 as high risk. The traditional method yielded 24 failures with an RPN ≥300, of which 22 were identified as high risk by the simplified method (92% agreement). The top 20% of CI (≥60) included 12 failures, of which six were designated as high risk by the simplified method (50% agreement). Conclusions: These results suggest that the simplified method of scoring and ranking failures identified by an FMEA can be a useful tool for healthcare organisations with limited access to FMEA expertise. However, the simplified method does not result in the same degree of discrimination in the ranking of failures offered by the traditional method.